Corporate Sustainability Disclosure and Firm Value in Energy Companies: Pengungkapan Keberlanjutan Korporat dan Nilai Perusahaan dalam Perusahaan Energi - Firnanda Firnanda Kusumawati; Duwi Rahayu (Universitas Muhammadiyah Sidoarjo, 2025)
General Background Firm value is a central indicator of corporate performance and investor perception, particularly in capital-intensive industries. Specific Background Energy sector companies face increasing scrutiny regarding sustainability practices, including corporate social responsibility and environmental accounting disclosures. Knowledge Gap Previous studies show inconsistent findings regarding the association between sustainability-related practices and firm value, especially within the energy sector context. Aims This study aims to examine the relationship between sustainability-related disclosures and firm value in energy sector companies listed on the Indonesia Stock Exchange. Results The empirical findings indicate that sustainability-related variables and financial characteristics jointly explain variations in firm value. Novelty This study provides sector-specific evidence by focusing on energy companies and integrating sustainability and financial variables within a single empirical model. Implications The results offer insights for corporate management and stakeholders in understanding firm value dynamics within sustainability-oriented business environments. Keywords: Firm Value, Energy Sector, Corporate Social Responsibility, Sustainability Disclosure, Green Accounting Key Findings Highlights: Sustainability-related disclosures are associated with firm value variation. Financial characteristics remain relevant in explaining valuation differences. Energy sector context strengthens the relevance of sustainability issues.